The Construction of Social Work Criminal Sanctions in Indonesian Criminal Law: Formulation and Orientation in Indonesian Criminal Law - Hadi, Adwi Mulyana; Fajrin, Yaris Adhial; Ishwara, Ade Sathya Sanathana (Faculty of Law, University of Mataram, 2023)
Social work criminal sanctions are one of the types of sanctions formulated in the New Criminal Code (NCC). Social work criminal sanctions are oriented towards providing a deterrent effect and educating convicts so that they do not repeat the crimes they have committed. This study focuses on the analysis of the construction of social work criminal sanctions in Indonesian criminal law. This type of research is normative legal research that emphasizes conceptual and statutory approaches. The results of the study show that the concept of the formulation of social work criminal sanctions in the NCC is actually based on the theory of punishment which is retributive in nature, namely it aims to provide a deterrent effect for perpetrators of criminal acts. Social work criminal sanctions in the NCC are also an implementation of an integrative punishment system that emphasizes the human dimension and is oriented towards making convicts part of society. The orientation of social work criminal sanctions in the NCC should be carried out while guaranteeing convicts' rights and community participation to oversee the implementation of social work criminal sanctions. Suggestions from this study are the need for guidelines and technical guidelines for the implementation of social work criminal sanctions so that they can guide law enforcement officials in carrying out social work criminal sanctions.